Painful ulcerations associated with COVID-19 in an adolescent patient: a case report - Danesh, David O.; Lee, Kyulim; Wallihan, Rebecca G.; Townsend, Janice A.; Mulo, Ira; Kumar, Ashok (Frontiers in Dental Medicine, 2024)
Oral manifestations lesions associated withof SARS-CoV-2 (COVID-19) include aphthous-like ulcers, herpetiform eruption of vesicles and erosions on lips, anterior tongue and buccal mucosa, Candida-associated lesions, recurrent herpesvirus infection, blisters, dark pigmentations, erythema multiforme-like lesions, white plaques, yellowish ulcers, inflammatory and purulent areas on pharyngeal wall, sialadenitis, overgrowth of filiform papillae, tongue depapillation, necrotizing gingivitis, salivary gland infections, angular cheilitis, hyposalivation, xerostomia, burning mouth sensation, facial pain, and oral submucous fibrosisand other findings. Reactive infectious mucocutaneous eruption (RIME) has recently been used to describe non-Mycoplasma . pneumoniae pathogens that can lead to rash and mucositis. RIME secondary to SARS-CoV-2 infection is consistent with reports in the literature. The patient in this case report is significant in that it involves only the oral mucosa, although there are cases reported where mucosal involvement is limited to one site. The degree of mucosal involvement in our case report was in the presence of an acute COVID-19 infection without ocular or genital involvement. Oral manifestations lesions of associated with COVID-19 infection vary in presentation. This paper adds to the understanding of systemic manifestations of COVID-19 infection and provides a reference of clinical findings, management, and interdisciplinary collaboration for caring for this patient.